2020
DOI: 10.1371/journal.pone.0227307
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Z-number weighted averaging operators and their application to portfolio selection problem

Abstract: Z-numbers can generate a more flexible structure to model the real information because of capturing expert's reliability. Moreover, various semantics can flexibly be reflected by linguistic terms under various circumstances. Thus, this study aims to model the portfolio selection problems based on aggregation operators under linguistic Z-number environment. Therefore, a multi-stage methodology is proposed and linguistic Z-numbers are applied to describe the assessment information. Moreover, the weighted averagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 67 publications
(86 reference statements)
0
26
0
Order By: Relevance
“…From Table 9, it can be found that the assets selected by LZBM and LZGBM operators are slightly different from the assets obtained by LZWA, LZOWA and LZHWA operators [40]. This difference displays an advantage of the proposed aggregation operators which capture the interrelationship between input arguments, while Mahmoodi et al methods [40] suppose the input arguments are independent.…”
Section: E Comparison With Mahmoodi Et Al Methods [40]mentioning
confidence: 93%
See 2 more Smart Citations
“…From Table 9, it can be found that the assets selected by LZBM and LZGBM operators are slightly different from the assets obtained by LZWA, LZOWA and LZHWA operators [40]. This difference displays an advantage of the proposed aggregation operators which capture the interrelationship between input arguments, while Mahmoodi et al methods [40] suppose the input arguments are independent.…”
Section: E Comparison With Mahmoodi Et Al Methods [40]mentioning
confidence: 93%
“…In order to further investigate the validity of the proposed aggregation operators, we compare them with Mahmoodi et al methods [40] built on some linguistic Z-number weighted averaging operators. The selected assets obtained by Model 2 are shown in Table 9.…”
Section: E Comparison With Mahmoodi Et Al Methods [40]mentioning
confidence: 99%
See 1 more Smart Citation
“…The central of this interval at the point α ab is a nominal value andâ ab is the perturbation of uncertain parameters α ab ,b 2 Λ a . Finally, robust counterpart of constraint a based on Soyster [108], Ben-Tal & Nemirovski [109] and Bertsimas & Sim [110] robust optimization approaches are proposed as Eqs (10) to (12), respectively:…”
Section: Robust Optimizationmentioning
confidence: 99%
“…Another point that should be considered in the proposed approach for portfolio construction is the uncertain nature of parameters [9][10][11][12]. Because in the real-world, we face uncertain data, and one of the most important features of financial markets is their embedded uncertainty.…”
Section: Introductionmentioning
confidence: 99%